Comparison of the physical education & sports teachers’ educational research attitudes with other teachers - Fatih Özgül; Murat Kangalgil; Rahmi Yıldız (Intelektual Pustaka Media Utama, 2021)
The aim of this research was to compare the attitudes of physical education and sports teachers and other branch teachers towards educational research. The sample group of the study was determined by convenient sampling method. The data of the study were collected from 304 teachers in different fields (152 Female, 152 Male; 102 of them are in 23-29 age group, 131 of them are in 30-36 age group and 71 of them are above 37 years). In the research,